Methaemoglobinaemia Can Complicate Normothermic Machine Perfusion of Human Livers - Tingle, Samuel J.; Ibrahim, Ibrahim; Thompson, Emily R.; Bates, Lucy; Sivaharan, Ashwin; Bury, Yvonne; Figuereido, Rodrigo; Wilson, Colin (Frontiers in Surgery, 2021)
Background: Although liver normothermic machine perfusion is increasingly used clinically, there are few reports of complications or adverse events. Many centres perform liver NMP to viability test suboptimal grafts, often for prolonged periods. In addition, several researchers are investigating NMP as a drug delivery platform, which usually necessitates prolonged perfusion of otherwise non-viable liver grafts. We describe two instances of methaemoglobinaemia during NMP of suboptimal livers. Methods: The NMP of eight human livers rejected for transplantation is described. Methaemoglobinaeima developed in two; one perfused using generic Medtronic™ perfusion equipment and one using the OrganOx Metra®. Results: The first liver (53yrs DBD) developed methaemoglobinaemia (metHb=2.4%) after 13 hours of NMP, increasing to metHb=19% at 16 hrs. Another liver (45yrs DBD) developed methaemoglobinaemia at 25 hrs (metHb=2.8%), which increased to metHb=28.2% at 38 hours. Development of methaemoglobinaemia was associated with large reductions in oxygen delivery and oxygen extraction. Both livers were steatotic and showed several suboptimal features on viability testing. Delivery of methylene blue failed to reverse the methaemoglobinaemia. Compared to a matched cohort of steatotic organs, livers which developed methaemoglobinaemia showed significantly higher levels of haemolysis at 12 hours (prior to development of methaemoglobinaemia). Conclusions: Methaemglobinaemia is a complication of NMP of suboptimal liver grafts, not limited to a single machine or perfusion protocol. It can occur within 13 hours (a timepoint frequently surpassed when NMP is used clinically) and renders further perfusion futile. Therefore, metHb should be monitored during NMP visually and using blood gas analysis.